2016
DOI: 10.1155/2016/2487924
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neuropathic Pain and Obesity

Abstract: Objectives. Overweight negatively affects musculoskeletal health; hence obesity is considered a risk factor for osteoarthritis and chronic low back pain. This was conducted to determine if obesity affects neuropathic pain, usually considered unrelated to the weight-load on the musculoskeletal system. Methods. Using a cut-off body mass index value of 25, 44 patients with neuropathic pain were grouped into a “high-BMI” group and a “normal-BMI” group. Results. The numeric rating scale of the high-BMI group was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
1
34
3
1
Order By: Relevance
“…49 Additionally, previous studies have found significant associations of obesity with muscle and nerve pain, including neuropathy and disorders of muscle ligaments. 50 Obesity is also associated with increased depression, pain perception, and disturbed sleep, 25,51−53 which could present additional pathways through which BMI affects chronic pain and opioid use. 54 Although increased chronic pain and prescription opioid use are closely associated with depression and poor mental health, this study revealed that adults living with obesity were at heightened risk for long-term prescription opioid use, even after adjusting for mental health.…”
Section: Discussionmentioning
confidence: 99%
“…49 Additionally, previous studies have found significant associations of obesity with muscle and nerve pain, including neuropathy and disorders of muscle ligaments. 50 Obesity is also associated with increased depression, pain perception, and disturbed sleep, 25,51−53 which could present additional pathways through which BMI affects chronic pain and opioid use. 54 Although increased chronic pain and prescription opioid use are closely associated with depression and poor mental health, this study revealed that adults living with obesity were at heightened risk for long-term prescription opioid use, even after adjusting for mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is usually associated with musculoskeletal system disorders such as back pain or osteoarthritis. Moreover, many studies indicate that it could be one of the risk factors in some nociceptive pain conditions, and more recently, it has been demonstrated that obesity is associated with worsening in neuropathic pain intensity (Hozumi et al, 2016). On the other hand, patients FIGURE 3 | Pain threshold by hot plate and tail flick test were performed at the end of CAF exposure (day 40) and during abstinence period (54 and 68 days).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the association between them found as low with biothesiometer and high positive correlation with NSS and NDS respectively this supports that there is a direct relation between the obesity and neuropathic pain this and the work done by Hozumi J et al, they had confirmed that obesity frequently tends to demonstrate limited activity of daily living and have suggested that the weight loss intervention might improve neuropathic pain severity. 20 Major strength of this epidemiological study compared with others is that it is substantially longer than any previously published study on the prevalence of DPN. Although Biothesiometry is a useful clinical tool for screening of neuropathy, its sensitivity is probably much lower than performing on nerve conduction studies for diagnosing neuropathy.…”
Section: Ndsmentioning
confidence: 93%